From Mesopotamia through Carroll Quigley to Bill Clinton: World Historical Systems, the Civilizationist, and the President - David Wilkinson (Journal of World-Systems Research, 1995)
The noted comparative civilizationist and world-historical systems analyst Carroll Quigley, whose theorizing rested on the whole historical span from Mesopotamia to the 1960's, was a teacher well-remembered by his student Bill Clinton.  Quigley, by an intensive process of reduction, or rather idealization, of masses of historical data, derived a procedure for the diagnosis and therapy of ailing civilizations/world-systems, especially the one which he inhabited.  The coherent, persistent and personal motifs of the policy discourse and variant initiatives of his student, the President, bear more than a passing resemblance to the hopeful, idealistic, voluntaristic, intellectual, scientific, economistic, demi-materialistic propensities of the civilizationist and teacher.